2014
DOI: 10.1603/en13128
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Density and Movement of theLygusspp. ParasitoidPeristenus relictus(Hymenoptera: Braconidae) in Organic Strawberries With Alfalfa Trap Crops

Abstract: Alfalfa trap crops are currently used to manage Lygus spp. in organic strawberry fields on the California Central Coast. The retention of Lygus spp. in alfalfa creates aggregated distributions that provide improved opportunities for biological control by the introduced parasitoid Peristenus relictus (Ruthe). The abundance and distribution of P. relictus between two trap crops separated by 50 strawberry rows were analyzed in 2008 and 2010. Parasitism of Lygus spp. nymphs by P. relictus (measured by larval abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…For instance, gaining a better understanding of how habitats with high prey densities (i.e., trap-crops) affect predator movement can clarify predator source/sink dynamics and thereby inform conservation biological control strategies (Lavandero et al, 2004). These data are similar to the dispersal results reported for Lygus and the Lygus-specific parasitoid, Peristenus relictus (Ruthe), by Swezey et al (2013Swezey et al ( , 2014. Overall, 62% (n = 550 out of 888) of all the focal predators captured from the centrally marked alfalfa contained the protein mark.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…For instance, gaining a better understanding of how habitats with high prey densities (i.e., trap-crops) affect predator movement can clarify predator source/sink dynamics and thereby inform conservation biological control strategies (Lavandero et al, 2004). These data are similar to the dispersal results reported for Lygus and the Lygus-specific parasitoid, Peristenus relictus (Ruthe), by Swezey et al (2013Swezey et al ( , 2014. Overall, 62% (n = 550 out of 888) of all the focal predators captured from the centrally marked alfalfa contained the protein mark.…”
Section: Discussionsupporting
confidence: 61%
“…Any predator testing positive for the presence of the mark was assumed to have originated from the centrally located, proteinmarked, alfalfa trap-crop. Additional information regarding the farm sites, protein marking protocols, collection methods, or ELISA techniques used in this study are provided by Swezey et al (2013Swezey et al ( , 2014. It should be noted that the negative control predator specimens were collected from nearby alfalfa fields prior to the application of the protein marks.…”
Section: Protein Mark Detectionmentioning
confidence: 99%
“…The backpack sprayer used here and by Swezey et al. () proved to be very effective at evenly distributing the protein treatments throughout the alfalfa canopy. Others have reported satisfactory results in protein marking efficiency in other types of crops using tractor‐mounted boom and nozzles (Horton et al.…”
Section: Discussionmentioning
confidence: 78%
“…; Swezey et al. ). However, marking efficiency data published to date also suggest that certain insects acquire and retain externally applied proteins more readily than others (Jones et al.…”
Section: Discussionmentioning
confidence: 97%
“…Horton et al 34 used an electric spray device mounted on an all-terrain vehicle to pinpoint applications of egg whites to insects occupying cover crops embedded in a pear orchard ( Figure 3F). Similarly, Swezey et al 5,35 used a backpack sprayer to apply precise applications of chicken egg whites to rows of an alfalfa trap crop (a preferred host plant) embedded in an organically grown strawberry field to mark a pest and its natural enemies ( Figure 3G). The results from that research showed that the pest and natural enemies were retained by the alfalfa trap crop and rarely dispersed into the highly valued strawberries.…”
Section: Introductionmentioning
confidence: 99%